Bilateral Trade of India with Middle East Countries : A Study of Iran - Gupta, Anuj; Kumar, Ravi (Journal of Commerce and Trade, 2016)
From the recent past, it has been seen that the structure of international trade is made simple & smoothening. India is having a good political, cultural & economic relationship with Iran. Iranian oil is very popular in India while the cereals & other food materials are popular in Iran. The need of present hour is to build stronger trade relation with Middle East nations, among them Iran is an important country. From the study it has been found that the trade balance is negative for India in the recent past. The share of total export to Iran is also very low. Hence, policies should be made to encourage this trade between the two nations. Oil is the chief commodity imported due to its natural superiority. An alternative use for oil must be developed to decrease the use of oil in the nation. Better export of arts & artifacts must be done to improve the quantity of export from India. Political relation must be made stronger to enhance the trading between the nations. Providing better environment to the exporters through subsidies, financial & technical assistance, etc. to enhance the total growth of export will be a better option.